2013
DOI: 10.18632/oncotarget.1412
|View full text |Cite
|
Sign up to set email alerts
|

Efficient induction of differentiation and growth inhibition in IDH1 mutant glioma cells by the DNMT Inhibitor Decitabine

Abstract: Mutation in the IDH1 or IDH2 genes occurs frequently in gliomas and other human malignancies. In intermediate grade gliomas, IDH1 mutation is found in over 70% of tumors. These mutations impart the mutant IDH enzyme with a neomorphic activity – the ability to synthesize 2-hydroxyglutarate (2-HG). This ability leads to a reprogramming of chromatin state, a block in differentiation, and the establishment of the glioma hypermethylator phenotype (G-CIMP). It has been hypothesized but not proven that the extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(174 citation statements)
references
References 19 publications
7
165
2
Order By: Relevance
“…The use of DNMT inhibitors in IDH-mutated cancers is motivated by the hypothesis that the oncogenic effects of IDH mutation are driven by its effects on the methylome. Two groups 65,66 have recently studied the DNMT inhibitors decitabine and 5-azacytidine in IDH-mutant glioma cell models.…”
Section: Dna Methyltransferase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of DNMT inhibitors in IDH-mutated cancers is motivated by the hypothesis that the oncogenic effects of IDH mutation are driven by its effects on the methylome. Two groups 65,66 have recently studied the DNMT inhibitors decitabine and 5-azacytidine in IDH-mutant glioma cell models.…”
Section: Dna Methyltransferase Inhibitorsmentioning
confidence: 99%
“…Turcan and colleagues 65 observed that the administration of decitabine to an IDH1 R132H mutant anaplastic astrocytoma cell line (TS603), while not affecting 2-HG levels, efficiently induced upregulation of differentiation genes, an effect associated with a change in methylation markers leading to reexpression of Polycombcontrolled genes. Remarkably, the differentiation effect was maintained even after drug therapy was stopped.…”
Section: Dna Methyltransferase Inhibitorsmentioning
confidence: 99%
“…Mutations in TET2 and isocitrate dehydrogenases IDH1 and IDH2 are seen in gliomas and leukemia (116)(117)(118)(119)(120)(121)(122), and IDH1 mutations in gliomas correlate with a DNA CpG island methylator phenotype (116,123). Preliminary encouraging data suggest that patients with mutations in these epigenetic regulators may particularly benefit from demethylating therapy, with preclinical studies showing decreased tumor growth and induction of tumor differentiation (124,125). More recently, mutations in the SWI/SNF chromatin remodeling complex, especially in the AT-rich interactive domain 1A (ARID1A), have also been identified in a multitude of solid cancers including pancreas, breast, ovarian, gastric, and colon (42,(126)(127)(128), although the relationship between ARID1A mutations and downstream cancer epigenome is still being elucidated.…”
Section: Figurementioning
confidence: 99%
“…Decitabine and 5-azacytidine are two very interesting DNMT inhibitors because they are well known FDA approved drugs that can pass the blood-brain barrier. Turcan et al observed that decitabine treatment promotes changes in methylation markers leading to the re-expression of differentiation genes, and long lasting differentiation effects [ 87 ]. Another group examined the impact of 5-azacytidine and a reported reversion of the G-CIMP state concomitant with the upregulation of differentiation genes and decreased tumor growth in vivo [ 88 ].…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%